Review of Clinical Studies on Karnini Yonivyapad vis-a-vis Cervical Erosion (International Journal of Ayurveda and Pharma Research, 2021)
Cervical erosion is a most common condition seen in women of reproductive age groups. Its prevalence is between 50-85% of all the gynecological conditions. In modern system of medicine diathermy cauterization or cryosurgery are generally advised for treatment but these procedures have their own side effects and complications like excessive vaginal discharge, secondary infertility, bleeding per vagina, infection, stenosis etc.. So still it is one of the most troublesome diseases for patients as well as for gynaecologists. Due to the serious consequences of the disease it is the need of hour to develop an accurate therapy for pathological erosion. This is an attempt to throw some more light on the clinical studies on cervical erosion. On cervical erosion total eight clinical studies in PG level has been completed out at National Institute of Ayurveda, Jaipur. Out of eight clinical studies, five works on Kshara Karma Karma (application of caustics), two works on Agnikarma (cauterization), two works on Kushthadi churna, one work on kushthadi varti, one work on Virechana. The drugs and procedures used in the research studies have chedana, Bhedan, Sosahana, Lekhana, Shodhana, Shothaghna, Raktprasadana, Vrana Shodhana (ulcer cleansing), Vrana Ropana (ulcer healer), krimihara, Kushtaghna (anti-dermatosis), Kandughna (anti-pruritic) properties. Maximum studies are carried out on Bahya Parimarjana (external application).